A rare case of survival after traumatic blunt ventricular rupture. Issue 2 (14th February 2023) - Yang, Ryan; Van Gent, Michael; Clements, Thomas; Cotton, Bryan; Wandling, Michael
Abstract: A male in his 40s presented to the trauma center via air ambulance after colliding with a cement wall at highway speeds. Cross-sectional imaging revealed a right ventricular pseudoaneurysm, confirmed by echocardiography. He was taken emergently to the operating room where he was found to have a pericardial laceration, hemopericardium and a right ventricular rupture, which was primarily repaired. Postoperatively, the patient was transferred to intensive care and after 34 days in the hospital was ultimately discharged home.